ESTIMATION OF WATER SATURATION IN CARBONATE RESERVOIRS WITHOUT RESISTIVITY LOG DATA. PART I: THEORY AND EXISTING MODEL - Bambang Widarsono; Heru Atmoko; Ridwan Ridwan; Kosasih Kosasih (Testing Center for Oil and Gas LEMIGAS, 2008)
This paper presents an observation over a suggested approach for establishing water saturation model that is specifically designed without the need of resistivity log data. One of the main strength of the approach is that the resulting water saturation model can be specifically established for local or specific use only. This is true since the approach can be applied using carbonate rocks that are obtained locally or from specific areas. Another important conclusion is that this approach can also be applied for any carbonate rock classification as long as the classification can clearly group carbonate rocks into groups with distinctive petrophysical properties. This paper – first part of two – presents theory and rock classification that underlines the approach, as well as procedure and the existing models available.